The New Testament - Bockmuehl, M; Kozitza, E (Oxford University Press, 2020)
This chapter examines several distinct strands in the New Testament’s reflection on Jesus’ Nativity: from the mystery surrounding his origins in the earliest Gospel, Mark, to the respective infancy narratives of Matthew and Luke, to John’s mystical language of the Word’s origins, and non-narrative conceptions of Jesus’ coming into the world in Paul, other letter-writers, and Revelation. It argues that the slender ancient accounts of ‘Jesus becoming Jesus’ nonetheless offer a rich tapestry of insights on the Incarnation at the heart of Christmas. Brief engagement with the early reception of these texts in theology and apologetics, literary production and art, devotion and liturgy, lend significant support to this conclusion.